Brexit w polityce europejskiej Niemiec - Koszel, Bogdan (Przegląd Politologiczny, 2018)
Since the beginning of David Cameron’s rule in the United Kingdom (2010) Eurosceptic sentiments have intensified, leading to a split in society, a referendum and, finally, Brexit. Germany was for the UK remaining in the EU, but after the referendum Germany announced the EU would negotiate hard to have its conditions met. Germany decided that Brexit provided favorable prospects for enhancing cooperation among the remaining 27 states. The most difficult negotiating items concern financial settlements between London and Brussels (ca. EUR 60 billion), the status of EU citizens employed and residing in the territory of the UK, and the North Ireland-Irish Republic border. The negotiations of a new trade agreement between the EU and the UK are also difficult.